A case of primary pulmonary leiomyosarcoma - Yoshiki Yata (Respiratory Medicine Case Reports, 2019)
Primary pulmonary leiomyosarcoma (PPL) is a very rare malignant tumor which arises from bronchial smooth muscle and vessels. We report 48-year-old male who was diagnosed to have a small lung nodule in the right upper lung field by chest X ray film (XP). A disk shape small nodule was identified in the posterior segment of the right upper lobe by chest CT. Transbronchial lung biopsy (TBB) specimen showed a cluster of dense spindle cells with irregular shape nucleus and some necrosis. 18FluoroDeoxyGlucosePositoron Emission CT (PET-CT) showed that the tumor had high value of the maximal standard uptake value (SUVmax) with no metastasis to the lymph nodes nor other organs. The right upper lobectomy and lymph node dissection were performed and microscopic examination of the specimen showed that the tumor was grade 2 leiomyosarcoma and there was no pleural invasion, nor lymph node metastasis. Post-operative staging of the tumor including its grade was Stage IIA. Immunohistochemical analysis of the specimen showed a clear transition from normal bronchial smooth muscle bundle to leiomyosarcoma in the bronchial wall. The bronchial vessels were fairly preserved. These finding suggested that the leiomyosarcoma developed from bronchial smooth muscle.